20.3k views
1 vote
Write a p if the sum is positive and a n if the sum is negative

1. (+6) + (-5) =
2. (+6) + (-9 =
3. (-6) + (-4) =
4. (+6) + (-2) =
what is each sum
1. (-7) + (+1) + (+2) =
2. (-2) + (-4) + (+3) =
3. (+5) + (+3) + (-1) + (-4) =
4. (-4) + (+3) + (-2) + (-6) =



1 Answer

3 votes

Answer:

[see below]

Explanation:

For Part 1:

(+6) + (-5) = 6 - 5 = 1 (P)

(+6) + (-9) = 6 - 9 = -3 (N)

(-6) + (-4) = -6 - 4 = -10 (N)

(+6) + (-2) = 6 - 2 = 4 (P)

Part 2:

(-7) + (+1) + (+2) = -7 + 1 + 2 = -4

(-2) + (-4) + (+3) = -2 - 4 + 3 = -3

(+5) + (+3) + (-1) + (-4) = 5 + 3 - 1 - 4 = 3

(-4) + (+3) + (-2) + (-6) = -4 + 3 -2 - 6 = -9

Hope this helps.

User GGamba
by
6.0k points